Process Safety Management (PSM) for managing contractors in process plant - Abdul Majid, N.D. (Elsevier Ltd, 2015)
Accidents involving contractors continue to occur with regular frequency. By using the standard set within the PSM 29 CFR 1910.119(h) regulations, it has been identified that certain aspects of the way contractors do work are not up to the stipulated regulatory requirements especially regarding matters like not providing mandatory personal protective equipment (PPE) to the workers, not discussing hazards related to handling procedures with the workforce and improper control of non-routine activities during changes in shifts. The PSM 29 CFR 1910.119(h) regulations promulgated in 1992 provides standards that covered processes to obtain and evaluate data regarding contractors' health and safety programs as well as the contractors' performance evaluation. Many of the accidents involving contractors are direct result of poor training of contractors and/or poor control of the contracted work. Even though most organizations have their own contractor management systems, there are issues in meeting the requirements of PSM. The PSM standard only state "what to do" not "how to do it". This is known as self-regulatory policy which depends on the industries understanding to interpret the standard that also contribute to this problem. This paper presents a structured and easy technique to plan and implement a practical and comprehensive contractors' management system in process industries that will comply with OSHA CFR 1910.119. A model has been developed based on this technique and its application has been tested in a pilot plant for compliance to PSM regulation. The model is beneficial to the process industries as any deficiencies in the PSM contractors' management program will be highlighted by the model which will then easily correct the identified deficiency so as to minimize and prevent catastrophic accidents. Â© 2015 Elsevier Ltd.